The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/20008198.2017.1283086
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptom severity relates to cognitive and psycho-social dysfunctioning – a study with Congolese refugees in Uganda

Abstract: Background: In the ongoing conflict in the Democratic Republic of the Congo (DRC), civilians have been heavily exposed to traumatic stressors. Traumatizing experiences cumulatively heighten the risk for trauma-related disorders, and with it affect cognitive and psycho-social functioning. Objectives: We aimed at investigating the association between trauma-related disorders and cognitive and psycho-social functioning and hypothesized that PTSD symptom severity would negatively correlate with executive functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 55 publications
5
38
0
Order By: Relevance
“…The majority of participants reported that they had lacked food, water, or shelter; stayed in a war zone; or experienced a violent attack by strangers, imprisonment, or torture. The reported traumatic experiences were similar to those reported by other refugees who had to leave their homes due to war and political violence (e.g., Ainamani, Elbert, Olema, & Hecker, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…The majority of participants reported that they had lacked food, water, or shelter; stayed in a war zone; or experienced a violent attack by strangers, imprisonment, or torture. The reported traumatic experiences were similar to those reported by other refugees who had to leave their homes due to war and political violence (e.g., Ainamani, Elbert, Olema, & Hecker, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…It examined the pathophysiological mechanisms of the visual working memory in trauma survivors. Importantly, the current work used a model that predicts visual working memory and further studied the neuromechanisms of visual working memory in the distributed network of brain regions of trauma survivors, laying the foundation for RDoC [56]. This study found that visual working memory was negatively correlated with the severity of PTSD symptoms (see Additional file 1: Part 9).…”
Section: Discussionmentioning
confidence: 94%
“…The Institutional Review Board of the Mbarara University of Science and Technology as well as the Ugandan National Council for Science and Technology approved the study. Other results from this extensive data assessment are presented by Hecker et al (2015) and by Ainamani, Elbert, Olema, and Hecker (2017).…”
Section: Methodsmentioning
confidence: 99%